Odpowiedzi

2010-03-08T20:02:15+01:00
A) 3(x-7)-2(3x-1)=3x-21-6x+2=-3x-19
b) 6(x+5)-(2x+4)+(5x+1)=6x+30-2x-4+5x+1=9x+27
c) 8x+4x/2-6x-12/3=8x+2x-6x-4=4x-4
d) 12x-16/6+9x+31/3=12x+9x-16/6+62/6=21x+78/6=21x+13
e) 10x-16/2-50x-30/10=-40x-11
Najlepsza Odpowiedź!
2010-03-08T20:17:34+01:00
A) 3(x-7)-2(3x-1)= 3x- 21 - 6x+2= - 3x - 19
b) 6(x+5)-(2x+4)+(5x+1)= 6x+ 30 - 2x-4 + 5x+1=9x + 27
c) 8x+4x/2-6x-12/3=8x+2x-6x-4=4x+4
d) 12x-16/6+9x+31/3=12x+9x-16/6+62/6=21x+78/6=21x+13
e) 10x-16/2-50x-30/10= -60x-8-3=-40x-11
2010-03-08T20:41:16+01:00
A) 3(x-7)-2(3x-1)= 3x-21-6x+2 = -3x-19
b) 6(x+5)-(2x+4)+(5x+1)= 6x+30-2x-4+5x+1 = 9x+27
c) 8x+4x/2-6x-12/3= 8x+2x-6x-4 = 4x-4
d) 12x-16/6+9x+31/3= 12x+9x-16/6+62/6 = 21x+78/6 =2 1x+13
e) 10x-16/2-50x-30/10= -40x-11